2020
DOI: 10.3390/ijms21207436
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional Regulation of Vimentin Intermediate Filaments to Caveolin-1

Abstract: Both the mechanosensitive vimentin cytoskeleton and endocytic caveolae contribute to various active processes such as cell migration, morphogenesis, and stress response. However, the crosstalk between these two systems has remained elusive. Here, we find that the subcellular expression between vimentin and caveolin-1 is mutual exclusive, and vimentin filaments physically arrest the cytoplasmic motility of caveolin-1 vesicles. Importantly, vimentin depletion increases the phosphorylation of caveolin-1 on site T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…This speculation is coincided with our results that inhibiting the motor activity of myosin II significantly weakens the movement of the cytoplasmic CAV-1 vesicles (Figures 2C-E). Previous work by us reveals that vimentin intermediate filaments (IFs) function as physical barriers to restrain the intracellular trafficking of CAV-1 vesicles (Jiu, 2018;Shi et al, 2020). It is thus possible that the overall integrity and motility pattern of the cytoplasmic CAV-1 are comprehensively regulated by both actin and IFs cytoskeletal networks.…”
Section: Discussionmentioning
confidence: 99%
“…This speculation is coincided with our results that inhibiting the motor activity of myosin II significantly weakens the movement of the cytoplasmic CAV-1 vesicles (Figures 2C-E). Previous work by us reveals that vimentin intermediate filaments (IFs) function as physical barriers to restrain the intracellular trafficking of CAV-1 vesicles (Jiu, 2018;Shi et al, 2020). It is thus possible that the overall integrity and motility pattern of the cytoplasmic CAV-1 are comprehensively regulated by both actin and IFs cytoskeletal networks.…”
Section: Discussionmentioning
confidence: 99%
“…One manuscript included in this Special Issue increased the knowledge regarding this still open field by describing that vimentin physically repressed the motility of cytoplasmic Cav-1 vesicles and inhibited the phosphorylation level of Cav-1, thereby modulating the role of Cav-1 on migration and wound healing. On the contrary, these authors showed that Cav-1 did not have a significant effect on the transcriptional, translational, post-translational modification, subcellular expression, and dynamics of vimentin [8].…”
mentioning
confidence: 81%
“…The most well-studied relationship is between Cav1 and vimentin, which is associated with integrins at focal adhesions. Although there is a cell-dependent regulation of vimentin expression by Cav1 [ 203 , 204 , 205 ], a clear unidirectional regulation of vimentin on Cav1 has been reported. Vimentin depletion facilitates Cav1 mobilization and increases Y14Cav1 phosphorylation [ 187 , 201 , 205 , 206 ].…”
Section: Interaction Between Caveolae and Cytoskeletonmentioning
confidence: 99%